1993
DOI: 10.2514/3.11495
|View full text |Cite
|
Sign up to set email alerts
|

Role of hydrogen/air chemistry in nozzle performance for a hypersonic propulsion system

Abstract: A computer model for describing quasi-one-dimensional flow of a gas mixture with area change and finiterate chemical reactions was used to study the role of hydrogen/air chemistry in nozzle performance for a hypersonic propulsion system. The important results obtained for a typical nozzle at a Mach 18 flight condition are as follows: 1) finite-rate chemistry should not be neglected in nozzle performance simulations because beneficial chemical processes persist throughout the entire nozzle length; 2) termolecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 7 publications
2
12
0
Order By: Relevance
“…5, the ratio was 0⋅956. This is in accord with previous investigations (3)(4)(5)(6)(7) , where nozzle freezing caused only a small loss in thrust.…”
Section: Numerical Modellingsupporting
confidence: 93%
See 1 more Smart Citation
“…5, the ratio was 0⋅956. This is in accord with previous investigations (3)(4)(5)(6)(7) , where nozzle freezing caused only a small loss in thrust.…”
Section: Numerical Modellingsupporting
confidence: 93%
“…An early study (3) of freezing of hydrogen-air chemical recombination in a ramjet thrust nozzle, where the expansion takes place from a low subsonic Mach number, showed that if equilibrium flow is maintained past the low supersonic area ratios the loss in thrust caused by chemical freezing is not exceedingly high. In later numerical studies of scramjet thrust nozzles at high flight Mach numbers, where the nozzle expansion takes place from supersonic Mach numbers, it was shown that although molecular vibration was in equilibrium throughout the nozzle, the chemical composition was not (4) , that at precombustion pressures of the order of an atmosphere there was little recombination in the nozzle (5) and that, in spite of this, the lack of complete recombination yielded an overall thrust which was only 1% less than the value for an equilibrium expansion (6) . Also, a study of thrust loss mechanisms in scramjets (7) showed that nozzle freezing represented only a small fraction of the overall losses.…”
Section: Introductionmentioning
confidence: 99%
“…Key among these are: the adjustment of the duct and inlet geometry as a function of flight Mach number; mixing of fuel with the air while controlling pre-ignition; conversion of gas chemical energy to kinetic energy within the exhaust nozzle (Harradine et al 1990 andSangiovanni et al 1993). Key among these are: the adjustment of the duct and inlet geometry as a function of flight Mach number; mixing of fuel with the air while controlling pre-ignition; conversion of gas chemical energy to kinetic energy within the exhaust nozzle (Harradine et al 1990 andSangiovanni et al 1993).…”
Section: Reactantsmentioning
confidence: 99%
“…Research on chemical non-equilibrium flow is mostly concentrated in the axisymmetric convergentdivergent nozzle. A computer model for describing quasi-onedimensional flow was used by Sangiovanni [1] to study the role of hydrogen/air chemistry in nozzle performance for a hypersonic propulsion system. The study shows that finite-rate chemistry should not be neglected in nozzle performance simulations because beneficial chemical processes persist throughout the entire nozzle length.…”
Section: Introductionmentioning
confidence: 99%